Risk performance of Stein-rule estimators over the least squares estimators of regression coefficients under quadratic loss structures - Shalabh; Helge Toutenburg; Christian Heumann (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2006)
This paper presents a general loss function under quadratic loss structure and discusses the comparison of risk functions associated with the unbiased least squares and biased Stein-rule estimators of the coefficients in a linear regression model.
urn:nbn:de:bvb:19-epub-1863-7
Keywords: 519